Tourism development model post the Covid-19 pandemic: Government policy perspective - Prasetya, Arik; Prakasa, Yudha; Edityastono, Lintang (Technium Social Sciences Journal, 2022)
The tourism sector is one of the strategic and potential sectors in national and regional economic development. As a country with natural and cultural resources, Indonesia has enormous potential to build and develop the tourism industry. The Covid-19 Pandemic caused the tourism sector to experience a significant decline. Besides, the Covid-19 Pandemic also provided opportunities and time for the government to rearrange tourism institutions to be even better. The research aims are the identification of superior tourism potential in Lumajang Regency, supporting and inhibiting factors for tourism development in Lumajang Regency, and adaptive tourism development strategies in Lumajang Regency in the new normal era. This study is descriptive with a qualitative approach to analyze the policy strategies that need to be implemented by local governments to increase the competitiveness of tourism based on superior potential in the post-Covid 19 pandemics: locus research at Lumajang Regency, East Java, Indonesia. The results show that Lumajang Regency has 37 tourist destinations that provide and contribute to locally generated revenue. However, there is no transparent integration model between the Local Government Agencies and other stakeholders, so tourism development still seems partial. In line with the increasingly competitive development of the tourism industry, tourism development must be encouraged to develop more strongly and be directed appropriately to increase the comparative advantage and competitive advantage of tourism in Lumajang Regency in the post the Covid-19 Pandemic. In addition, the study results indicate that tourism development in Lumajang Regency is still not optimal due to the weakness of tourism organization institutions. Efforts to strengthen these institutions can be carried out in four stages of action plans, namely human and institutional development, destination quality development, marketing development, and strengthening the tourism industry structure. The four stages consider aspects of the CHSE (Clean, Health, Safety, and Environmental Sustainability) standard for the tourism sector. The Covid-19 Pandemic has provided momentum for the Lumajang Government to strengthen tourism management.